Pullout performance of innovative polymer vertical anchor plates in layered soils - Alireza Parsa; Hamed Niroumand; Lech Balachowski (Scientific Reports)
Abstract This study explores the innovative use of polymer plate anchors in geotechnical engineering, addressing some of the limitations of traditional steel plate anchors. We investigated the performance of polymer vertical anchor plates in multi-layered cohesionless soils, focusing on the pullout capacity under various conditions. The research evaluated the effects of soil density, number of layers, and anchor embedment depth on the pullout performance. Experiments were conducted in a container filled with sand at two different densities (dense and loose) up to a height of 80 cm. A total of 12 tests were performed with varying embedment depths. Results indicated that increasing the distance of the polymer anchor from the soil wall significantly enhanced the pullout force, with a threefold increase observed at greater depths. The study concludes that soil parameters and anchor embedment geometry are critical factors influencing the pullout behavior of polymer anchors, highlighting the potential of polymer materials in anchor plate design.